2003
DOI: 10.1067/mhn.2003.88
|View full text |Cite
|
Sign up to set email alerts
|

Composite Chondroperichondrial Clip Tympanoplasty: The Triple “C” Technique

Abstract: The described technique provides an effective method of closing nonmarginal perforations of the tympanic membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Tos [14] classified cartilage techniques for tympanoplasties into 6 groups that can be categorized into 2 main techniques: the palisade technique and island graft technique. Fernandes [5] and Ahmed et al [15] introduced the “triple C” technique, which resulted in 100% and 91.3% graft success rates, respectively. Genc [16] described the perichondrium-preserved palisade island graft technique for tympanoplasty with a 93.61% success rate, while Larrosa et al [17] found no obvious difference in hearing or graft take results obtained with the palisade cartilage graft technique compared to the endoscopic chondroperichondrial graft technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tos [14] classified cartilage techniques for tympanoplasties into 6 groups that can be categorized into 2 main techniques: the palisade technique and island graft technique. Fernandes [5] and Ahmed et al [15] introduced the “triple C” technique, which resulted in 100% and 91.3% graft success rates, respectively. Genc [16] described the perichondrium-preserved palisade island graft technique for tympanoplasty with a 93.61% success rate, while Larrosa et al [17] found no obvious difference in hearing or graft take results obtained with the palisade cartilage graft technique compared to the endoscopic chondroperichondrial graft technique.…”
Section: Discussionmentioning
confidence: 99%
“…Most surgical methods for repair of tympanic membrane (TM) perforation are associated with a success rate of over 90%. [5] Temporalis fascia and cartilage are the commonly used autografts for myringoplasty. In the last 20 years, various studies have demonstrated that stiffness of cartilage helps achieve better stability and long-term uptake than fascia, making it a better choice in some difficult situations, such as poor eustachian tube function, infection, anterior perforation, and revision surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Tragal cartilage with perichondrium fulfills all the required qualities of an ideal graft material namely low rejection rate, sufficient quantity, good tensile strength, conductive properties similar to that of tympanic membrane and easy availability. Fernandes from Newcastle, Australia published the technique of composite chondroperichondrial clip tympanoplasty using the tragal cartilage 10 . Tragal cartilage is a fibroelastic cartilage and being composed of collagen type II is also similar nature of the tympanic membrane, temporal muscle fascia consists primarily of collagen type I. Collagen type II has higher tensile strength than other types.…”
Section: Introductionmentioning
confidence: 99%
“…3 A variety of myringoplastic techniques have been described in the literature including: the underlay, overlay technique, the technique 'Gelfilm Sandwich,' 'Swinging Door' technique, 'C' technique, the double-swing technique, 'fascible stitching' technique, the anterior anchor technique, the 'spot welding' technique assisted by laser. [4][5][6][7][8][9] The "underlay" and the "overlay" technique are two of the most frequent methods to position the graft relative to the remains of the tympanic membrane and the tympanic annulus. 10 The former is widely used and can be done relatively easily since the graft is placed completely in the medium of the remaining drum (or annulus) and manubrium.…”
Section: Introductionmentioning
confidence: 99%